Maternal fructose–induced oxidative stress occurs via Tfam and Ucp5 epigenetic regulation in offspring hippocampi. Issue 10 (17th July 2019) - Yamada, Hiroya; Munetsuna, Eiji; Yamazaki, Mirai; Mizuno, Genki; Sadamoto, Nao; Ando, Yoshitaka; Fujii, Ryosuke; Shiogama, Kazuya; Ishikawa, Hiroaki; Suzuki, Koji; Shimono, Yohei; Ohashi, Koji; et al.
ABSTRACT: Fructose consumption is rising globally, but maternal high fructose intake might adversely affect offspring. Our previous report demonstrated that excess maternal fructose intake impairs hippocampal function in offspring, indicating that the hippocampi of offspring are highly sensitive to maternal fructose. Here, we examined the effect of maternal high fructose on mitochondrial physiology and uncoupling protein (UCP) expression. Rat dams received a 20% fructose solution during gestation and lactation. Immediately after weaning, offspring hippocampi were isolated. Maternal high fructose consumption attenuated the mitochondrial O2 consumption rate and stimulated lipid hydroperoxide production in the hippocampi of offspring. Reduced Ucp5 and mitochondrial transcription factor A ( Tfam ) mRNA levels were also observed after maternal exposure to fructose. We assessed the promoter regions of both genes and found that this treatment enhanced DNA methylation levels. In addition, luciferase assays showed that this DNA methylation could reduce the transcription of both genes. Chromatin immunoprecipitation analysis demonstrated that specificity protein 1 binding to the Ucp5 promoter regions was reduced by DNA methylation. In addition, Ucp5 knockdown induced the up‐regulation of reactive oxygen species levels in a rat brain glioma cell line, whereas reduced O2 consumption was observed with Tfam knockdown. Maternal high fructose intake thus induces reduced O2 oxygen consumption and increases oxidative stress in offspring, at least partly through epigenetic mechanisms involving Ucp5 and Tfam .—Yamada, H., Munetsuna, E., Yamazaki, M., Mizuno, G., Sadamoto, N., Ando, Y., Fujii, R., Shiogama, K., Ishikawa, H., Suzuki, K., Shimono, Y., Ohashi, K., Hashimoto, S. Maternal fructose‐induced oxidative stress occurs via Tfam and Ucp5 epigenetic regulation in offspring hippocampi. FASEB J. 33, 11431–11442 (2019). www.fasebj.org